Effects of Compound Probiotics on Cecal Microbiome and Metabolome of Shaoxing Duck - Sun, Hanxue; Du, Xizhong; Zeng, Tao; Ruan, Shenggang; Li, Guoqin; Tao, Zhengrong; Xu, Wenwu; Lu, Lizhi (Frontiers in Microbiology, 2022)
This experiment was conducted to investigate the effects of compound probiotics on iinal microflora and metabolome of Shaoxing ducks. A total of 640 1-day-old Shaoxing ducks were randomly divided into two treatments with eight replicates and forty ducks for each replicate. The ducks were fed basal diet (Ctrl) and basal diet supplemented with 0.15% compound probiotics (MixP). The experiment lasted for 85 days. The results showed that the abundance of Bacteroidetes and Bacteroides in MixP was higher than that in Ctrl (P < 0.05). However, the abundance of Firmicutes and Oscillospira and Desulfovibrio in MixP was lower than that in Ctrl (P < 0.05). Concentrations of 71 metabolites differed significantly (P < 0.05) between the MixP and the Ctrl groups; for example, Pyridoxal (Vitamin B6), L-Arginine, and Betaine aldehyde were up-regulated (P < 0.05), and 7-oxocholesterol, 3-hydroxy-L-kynureni- ne, and N-acetyl-d-glucosamine were down-regulated (P < 0.05). KEGG was enriched in 15 metabolic pathways. The pathways of Vitamin B6 metabolism, Vascular smooth muscle contraction, Vitamin digestion and absorption, and Protein digestion and absorption were influenced by compound probiotics supplementation. Thus, supplementation of compound probiotics improved cecal heath through shifts in the cecal microbiome and metabolome.